A Randomized Sham-controlled Trial of 1-Hz and 10-Hz Repetitive Transcranial Magnetic Stimulation (rTMS) of the Right Dorsolateral Prefrontal Cortex in Civilian Post-traumatic Stress Disorder: Un essai randomisé contrôlé simulé de stimulation magnétique transcrânienne repetitive (SMTr) de 1 Hz et 10 Hz du cortex préfrontal dorsolatéral droit dans le trouble de stress post-traumatique chez des civils. (November 2020) - Leong, Kawai; Chan, Peter; Ong, Larry; Zwicker, Amy; Willan, Sharon; Lam, Raymond W.; McGirr, Alexander
Objective: Despite effective psychological and pharmacological treatments, there is a large unmet burden of illness in post-traumatic stress disorder (PTSD). Repetitive transcranial magnetic stimulation (rTMS) is a noninvasive intervention and a putative treatment strategy for PTSD. The evidence base to date suggests that rTMS targeting the dorsolateral prefrontal cortex (DLPFC), in particular the right DLPFC, leads to improvements in PTSD symptoms. However, optimal stimulation parameters have yet to be determined. In this study, we examine the efficacy of high- and low-frequency rTMS of the right DLPFC using a randomized, double-blind, sham-controlled design in civilian PTSD. Methods: We conducted a 2-week single-site randomized sham-controlled trial of rTMS targeting the right DLPFC. We recruited civilians aged 19 to 70 with PTSD and randomized subjects with allocation concealment to daily 1-Hz rTMS, 10-Hz rTMS, or sham rTMS. The primary outcome was improvement in Clinician Administered PTSD Scale–IV (CAPS-IV). Secondary outcomes included change in depressive and anxiety symptoms. Results: We recruited 31 civilians with PTSD. One 1-Hz-treated patient developed transient suicidal ideation. Analyses revealed significant improvement in CAPS-IV symptoms in the 1-Hz group relative to sham (Hedges' g = −1.07) but not in the 10-Hz group. This was not attributable to changes in anxious or depressive symptomatology. Ten-Hz stimulation appeared to improve depressive symptoms compared to sham. Conclusion: Low-frequency rTMS is efficacious in the treatment of civilian PTSD. Our data suggest that high-frequency rTMS of the right DLPFC is worthy of additional investigation for the treatment of depressive symptoms comorbid with PTSD.